Diltiazem for clozapine-induced generalized hyperhidrosis - Kenton Emma M. PharmD; Zoellner Samantha M. PharmD Candidate, May 2024; Nelson Leigh Anne PharmD, BCPP (Mental Health Clinician, 2023)
Background Clozapine can be associated with significant side effects and tolerability issues. Hyperhidrosis occurs less commonly and is unanticipated by clinicians because of clozapine's significant anticholinergic activity. Case Report A 34-year-old female developed clozapine-induced nocturnal, generalized hyperhidrosis following initial titration to 400 mg/day. Dose reduction did not decrease the side effect. Treatment with an anticholinergic medication could not be initiated because of constipation. Treatment with a beta blocker resulted in worsening of asthma. Treatment with a calcium channel blocker, diltiazem CD 180 mg/day, resulted in a significant reduction in hyperhidrosis. Conclusion This case supports the use of calcium channel blockers to reduce clozapine-induced hyperhidrosis and offers an alternative to anticholinergic medications that may negatively impact clozapine tolerability.